Analisis Muatan Dimensi Bernalar Kritis pada Modul Ajar Guru Kelas IV SD Negeri 62 Sungai Raya - Siti, Siti; Afryaningsih, Yunika; Setyowati, Dessy (HORIZON: Indonesian Journal of Multidisciplinary, 2024)
This study aims to analyze the content of the critical reasoning dimension in the teaching module of grade IV teachers of SD Negeri 62 Sungai Raya. This research is descriptive research with a qualitative approach. This study obtained data from the content of the critical reasoning dimension sourced from the teaching module of grade IV elementary school teachers. The logical dimension used is obtaining and processing information and ideas, analyzing and evaluating reasoning, reflecting, and evaluating. The data collection techniques used are observation, questionnaires, and interviews. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study concluded that for the elements of obtaining, processing information and ideas, the modules that still need to be improved are the Indonesian, Mathematics and PPKn modules. Then for the elements of analyzing and evaluating reasoning, the modules that need to be improved are the Indonesian, Mathematics, and PPKn modules. The reflecting element, the modules that still need to be improved are the Indonesian, Mathematics and PPKn modules. As for the next element, namely evaluating elements, only 1 module still needs to be improved, namely the PPKn module